The genetic basis of kidney cancer - Linehan, W. Marston (Henry Stewart Talks, 2014)
Renal Carcinoma, Stage I , Stage IV kidney cancer, Human Renal Epithelial Neoplasms, Loss of alleles in renal cell carcinoma, Mapping the Minimal 3p Loss Region in Clear Cell Renal Carcinoma, Studying Cancer Families to Identify Renal Carcinoma Genes, Identification of Kidney Cancer Genes, Inherited Forms of Renal Carcinoma, Clear Cell Renal Carcinoma: von Hippel Lindau (VHL), VHL Gene, VHL Gene Localization Map, Germline VHL Mutations, Papillary Renal Carcinoma, Mouse Studies of VHL gene, VHL Gene Function, HIFα, Downstream effects of VHL mutation, Targeting VHL/HIF in Clear Cell RCC, TCGA Clear Cell Kidney Cancer, Intratumor Heterogeneity, Warburg effect in clear cell kidney cancer, Non-Clear Cell RCC, Locally Advanced Kidney Cancer, Hereditary Papillary Renal Carcinoma (HPRC), Inherited Renal Carcinoma, Type 1 Papillary Renal Carcinoma, Penetrance of MET Mutation H1210R, MET Gene: Type 1 Papillary RCC, Location of the HPRC Gene, HPRC: Activating Mutations in the Tyrosine Kinase Domain of MET, Location of MET Mutations in the HPRC Patients, Targeting MET RCC Gene Pathway, Potential Small Molecule Target: MET Tyrosine Kinase Inhibition, Foretinib: Dual VEGFR and MET Inhibitor, MiT Kidney Cancer TFE3, TFEB, MITF, UOK124, Papillary Kidney Cancer, UOK124, UOK120, UOK 146 & TFE3 Kidney Cancer, Inherited Renal Carcinoma Birt-Hogg-Dubé (BHD), Birt Hogg Dubé Cutaneous Manifestations, Kidney Tumors in BHD, BHD Renal Tumor Pathology, BHD Lung Cysts, Identification of the BHD Gene, Cutaneous Fibrofolliculomas, BHD Gene: Chromophobe RCC, BHD Gene Locus: Chromosome 17, BHD Protein Sequence, FLCN Mutation Spectrum, Therapeutic Approach: What Kind of Gene is FLCN?, BHD Gene Analysis in BHD-Associated RCC, Somatic mutations in renal tumors from BHD patients, UOK 257, BHD -/- RCC cell line Study, How Does the FLCN Gene Function?, Folliculin-FNIP1/2-AMPK Interactions, mTORC1/mTORC2 Activation: FLCN-Deficient Kidney Cancer, BHD Deletion Specifically in the Kidney, BHDf/d/KSPCre Mouse Kidney Study, Hereditary Leiomyomatosis Renal Cell Carcinoma (HLRCC), HLRCC: Cutaneous Manifestations, Uterine Leiomyomas, HLRCC: Papillary Kidney Cancer Type 2, Orangophilic Nucleoli + Perinucleolar Halos, Fumarate Hydratase Gene: HLRCC, UOK-262 Study, Loss of a Krebs Cycle Enzyme Can Lead to Kidney Cancer, Impaired citric acid cycle and “Warburg effect”, HLRCC-Renal Cancer: Glucose-Dependent, PET Scan, HLRCC novel treatment approaches, Kidney Cancer: a Metabolic Disease